GENRE STYLE OF CONSTITUTION - MALINOWSKA, Ewa (Comparative Legilinguistics, 2018)
In this paper I take the meaning of genre as a model of a specified type of text. Therefore, I consider genre as a pattern of the text, which consists of all its planes (formal, cognitive, pragmatic, axiological, stylistic). I am especially interested in the stylistic plane of a concrete communicative event, which is the current text of the fundamental law, i.e. of the Constitution of the Republic of Poland (1997). The constitution in the stylistic dimension is multi-colour. A normative dry imperious style is dominant, with a high frequency of orders, duties and rights, but contrary to the other genres of official and legal spheres, there are also strongly present elements of high, elaborative rhetoric style exe-cuted not only in the preamble, but also in the solemn acts of president’s and MPs’ oaths. These particular texts in the text underline the significance of the constitution as the most important legal act for the state community. The ideo-logical convictions of the legislative body have also an influence on the genre style of the constitution.